Rehabilitation of existing reinforced concrete fire tank (330 m3) and domestic water tank (860 m3) of Eton Tower Makati in Makati City, Philippines - Marcelino, Rainier Cruz (Animo Repository, 2017)
In a mixed-use development that houses commercial retails, hotel and office occupancies, one essential service components are the cistern tanks for fire use and domestic water. In this study, a forty-storey mixed-used building has been constructed on an existing two-storey office building with six-level basement floors in which the fire tank was already built from basement level 6 to basement level 3 while the domestic water tank was already built from basement level 6 to basement level 2. These cisterns have been existent for about 15 years and have found to be leaking due to presence of massive cracking and due to deterioration. The intent of this study is to present the methodologies of rehabilitation works of these cistern structures which are both made of reinforced concrete. The rehabilitation methodology for each tank structure is presented in different approaches. The fire cistern has found to have minor cracks where water seepage emanates from the tank walls. On the other hand, the domestic water cistern has shown severe cracks that water seepage on its tank walls are significantly strong. In addition, the latter tank has two chambers and the chamber wall is severely damaged that it is almost near collapse. The rehabilitation works presented in this study basically include innovative waterproofing system and strengthening of the tank structures considering that both tanks are located in a confined space.